KONFLIK ETNIS DI PESISIR TELUK TOMINI: TINJAUAN SOSIO-EKOLOGI POLITIK - Obie, Muhammad; Soetarto, Endriatmo; Sumarti, Titik; Saharuddin, Saharuddin (AL-TAHRIR, 2014)
Conflicts have colored human history and occurred in various places. The ranges of conflict vary, from international, national to local scales. There can be economical, political, territorial and other sorts of conflict. One example of common type of the conflicts in Indonesia is local ethnic conflict between Indonesian local government and Bajo ethnic over marine territory at Tomini bay. This research aims not only to analyze this conflict at Tomini bay area but also to explore its causes, types, and resolution. The research uses critical theory and applies historical sociology and case study. The data is analyzed through qualitative method. The research shows that the ethnic conflict at Tomini bay was stimulated by the local government decision to give a license to a timber company and fishing industry at the bay. This policy has threatened Bajo’s social and economic systems at the bay and triggered authority, economy and knowledge conflicts. Intensive dialogues have been conducted to resolve the conflicts but have not yielded significant resolution. The best solution to terminate the conflict and give legal certainty over the use of the bay area is that the conflicting zones must be mapped justly and all interests are accommodated equally.